Screening of castor (Ricinus communis L.) germplasm and inbred lines against Fusarium wilt (Fusarium oxysporum f.sp. ricini): Screening of castor (Ricinus communis L.) germplasm and inbred lines against Fusarium wilt (Fusarium oxysporum f.sp. ricini) - YAMANURA; R MOHAN KUMAR; C P MANJULA; V APURVA (Journal of Oilseeds Research, 2020)
Among the 73 entries screened against wilt of castor, 27 were highly resistant (0% wilt), 3 were resistant with < 20% wilt, 10 were moderately resistant (20.1 to 40% wilt), 14 were moderately susceptible (40.1 to 50 %), nine were susceptible and 10 were highly susceptible to Fusarium wilt.